Spectrum of inherited metabolic disorders in Malaysia. - Thong, M.K.; Yunus, Z.M. (2008)
Issues pertaining to the diagnosis and management of inborn errors of metabolism (IEM) in Malaysia included low awareness of atypical and variable presentations in IEMs leading to delayed diagnosis or treatment, absence of reliable population data on IEMs and involvement of multiple siblings in the same family due to consanguinity. The importance of careful family history taking and genetic counselling are emphasised. Selected testing of ill infants and children for IEM yielded a positive 2% (264/13,500) results for IEMs in Malaysia. Out of the 264 patients, the spectrum of IEMs in Malaysia included organic acidurias (98), aminoacidopathies (78), urea cycle defects (54), neurotransmitter conditions (12) and lysosomal disorders, mainly mucopolysaccharidosis (14). Confirmatory studies of IEMs are an important aspect of management of IEMs. There is a need for more metabolic specialists and funding for diagnosis and treatment of IEMs in Malaysia. Long-term care issues and cost-effectiveness of IEM therapy, supportive and preventive aspects will need further studies in Malaysia.